A kind of cerium dioxide in-situ linked Anderson type Mo-Fe anchored nitrogen-doped carbon nanotube and its preparation method and application

By using ceria in situ link Anderson-type Mo-Fe anchoring nitrogen-doped carbon nanotubes, CeO2-Anderson MoFe-N/C material was formed, which solved the shortcomings of POMs electrocatalysts in terms of catalytic efficiency, stability and electronic conductivity, and achieved efficient catalytic performance of oxygen reduction and hydrogen evolution reaction.

CN119612576BActive Publication Date: 2025-04-18INNER MONGOLIA UNIVERSITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510147157.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-04-18
Estimated Expiration
2045-02-11

AI Technical Summary

Technical Problem

The existing polyoxygenate (POMs) electrocatalysts have shortcomings in catalytic efficiency, stability and electronic conductivity, which limits their application in technologies such as fuel cells.

Method used

Using cerium dioxide (CeO2) as the in-situ linker, the Anderson-type Mo-Fe precursor is assembled into a chain-like structure and efficiently combined with nitrogen-doped carbon nanotubes to form CeO2-Anderson MoFe-N/C material. This material enhances electron transfer capacity through the oxygen storage capacity of CeO2, and forms more nitrogen-containing active sites by stabilizing the nitrogen source, promoting oxygen reduction and hydrogen evolution reaction.

Benefits of technology

Highly efficient catalytic activity, stability and electron conductivity were achieved, the half-wave potential of the oxygen reduction reaction reached 0.90 V, the performance exceeded that of commercial Pt/C catalysts, and it showed excellent catalytic performance in the hydrogen evolution reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612576B_ABST
    Figure CN119612576B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of energy materials, and discloses a cerium dioxide in-situ linked Anderson type Mo-Fe anchored nitrogen-doped carbon nanotube and a preparation method and application thereof. The preparation method comprises: preparing Ce(OH) from ferric nitrate nonahydrate, cerium nitrate hexahydrate and ammonium molybdate tetrahydrate δ+ ‑Anderson MoFe precursor; then, through hydrothermal reaction, Ce(OH) δ+ ‑Anderson MoFe is uniformly grown on carbon nanotubes; finally, it is calcined at high temperature with melamine in N2 atmosphere to finally obtain CeO2‑Anderson MoFe‑N / C material. The preparation method of the present invention is simple, free of three wastes, environmentally friendly, and novel in structure. It provides a practical strategy for the development of high-performance, low-cost zinc-air battery materials, oxygen reduction reaction and hydrogen evolution reaction, and provides ideas for the design of efficient green energy storage devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of energy materials, and in particular to a cerium dioxide in-situ linked Anderson-type Mo-Fe anchored nitrogen-doped carbon nanotube and a preparation method and application thereof. Background Art

[0002] With the continuous growth of global energy demand and the severe challenges brought by climate change, finding clean and efficient alternative energy has become an urgent task for today's society. Fuel cells, as a promising new energy technology, have become one of the strong candidates to replace traditional fossil fuels with their high energy conversion efficiency and zero emissions. Especially driven by hydrogen as a clean energy source, oxygen reduction reaction (ORR) and hydrogen evolution reaction (HER) have become the core electrochemical reactions in technologies such as fuel cells and water electrolysis. However, despite the great potential of these reactions, their realization is restricted by slow reaction kinetics, especially in cathode reactions, where inefficient catalysts often lead to a significant reduction in energy conversion efficiency. Therefore, finding efficient, low-cost, and mass-producible electrocatalysts has become a hot topic in scientific research today.

[0003] At present, non-precious metal, bifunctional electrocatalysts have become the research focus to solve this problem. Polyoxometalates (POMs) have shown great potential in the field of electrocatalysis due to their unique structural advantages and electrochemical properties. POMs not only have adjustable electronic structure and stable redox properties, but also can effectively promote oxygen reduction reaction and hydrogen evolution reaction, making them ideal catalytic candidate materials. However, despite the good catalytic performance of polyoxometalates, they still face a series of challenges in practical applications. First, the catalytic activity of POMs is limited by its structural complexity and the limitation of surface active sites, resulting in the catalytic efficiency at higher current density cannot meet the needs of practical applications. Secondly, the stability and durability of POMs are still an urgent problem to be solved. During the long-term catalytic reaction, polyoxometalates may undergo structural changes or lose activity, especially under extreme acidic or alkaline conditions, which makes their application in practical environments challenging. More importantly, POMs usually have low electronic conductivity, which limits their performance as efficient electrocatalysts, especially in electrochemical reactions requiring high-speed electron transfer, where insufficient electronic conductivity reduces the catalytic efficiency. In addition, the synthesis method of POMs is also relatively complicated, involving multi-step reactions, finely controlled synthesis conditions and high-temperature treatment, which increases the difficulty and cost of its large-scale industrial production.

[0004] Therefore, although polyoxometalates have significant advantages in theory, the improvement of their catalytic performance, the improvement of stability and durability, and the problem of electronic conductivity are still the key bottlenecks restricting their application and promotion. Summary of the invention

[0005] In order to solve the above technical difficulties, the present invention proposes a new CeO2-Anderson MoFe-N / C material for use as an electrocatalyst, using CeO2 as an in-situ connector to successfully assemble the Anderson-type Mo-Fe precursor into a chain structure and efficiently combine it with nitrogen-doped carbon nanotubes. The catalyst utilizes the oxygen storage capacity of cerium dioxide (CeO2), enhances the electron transfer capacity and promotes the catalytic reaction, while stabilizing the nitrogen source, forming more nitrogen-containing active sites, and accelerating the oxygen reduction reaction and hydrogen evolution reaction. To this end, the purpose of the present invention is to provide a catalytic material that is simple to prepare, green and environmentally friendly, low-cost, and easy to operate, which is suitable for efficient reduction of oxygen and hydrogen evolution reactions. For the first time, a CeO2-Anderson MoFe-N / C material with a strip-shaped Anderson-type topological structure linked by CeO2 was synthesized in situ, which makes it tend to be the same as carbon tubes and is efficiently combined on the carbon wall through Mo-C bonds.

[0006] To achieve the above object, on the one hand, the present invention provides a method for preparing a cerium dioxide in-situ linked Anderson type Mo-Fe anchored nitrogen-doped carbon nanotube, which comprises: first preparing a structurally stable Ce(OH) δ+ -Anderson MoFe precursor; then through hydrothermal reaction, Ce(OH) δ+ -Anderson MoFe is uniformly grown on carbon nanotubes; finally, it is calcined at high temperature in a N2 atmosphere to finally obtain CeO2-Anderson MoFe-N / C material.

[0007] The specific steps of the preparation method of the present invention are as follows:

[0008] S1, dissolving ferric nitrate nine hydrate, cerium nitrate six hydrate and ammonium molybdate tetrahydrate in deionized water for reaction, centrifugation and drying to obtain Mo-based polyoxometalate Ce(OH) δ+ -Anderson MoFe material;

[0009] S2, adding glucose and carbon nanotubes into deionized water, and adding Ce(OH) δ+ -AndersonMoFe materials were mixed and reacted by hydrothermal synthesis. The reactants were washed and dried to obtain Ce(OH) δ+ -AndersonMoFe-N / C material;

[0010] S3, Ce(OH) δ+-Anderson MoFe-N / C material and melamine are fully ground and mixed evenly, and then calcined under N2 or inert atmosphere to obtain CeO2-AndersonMoFe-N / C material with a strip-shaped Anderson-type topological structure linked by CeO2, that is, Anderson-type Mo-Fe anchored nitrogen-doped carbon nanotubes in situ linked by ceria.

[0011] As a further preferred technical solution of the present invention, in step S1, ferric nitrate nonahydrate, cerium nitrate hexahydrate and ammonium molybdate tetrahydrate are first dissolved in boiling deionized water, and then reacted at 80°C-90°C.

[0012] As a further preferred technical solution of the present invention, in step S1, the dosage ratio of ferric nitrate nonahydrate, cerium nitrate hexahydrate, and ammonium molybdate tetrahydrate is 0.95~0.5 mol: 0.05~0.5 mol: 5.7~3 mol. Furthermore, the molar ratio of ferric nitrate nonahydrate to ammonium molybdate tetrahydrate is 1:6, and the molar ratio of ferric nitrate nonahydrate to cerium nitrate hexahydrate is preferably one of 0.95:0.05, 0.9:0.1, 0.8:0.2, 0.7:0.3, 0.6:0.4, and 0.5:0.5.

[0013] As a further preferred technical solution of the present invention, in step S2, the reaction temperature of the hydrothermal synthesis method is 180°C.

[0014] As a further preferred technical solution of the present invention, in step S2, the dosage ratio of carbon nanotubes, glucose and deionized water is 10-32 mg: 60-86 mg: 5-17 mL.

[0015] As a further preferred technical solution of the present invention, in step S3, Ce(OH) δ+ -The molar ratio of Anderson MoFe-N / C material to melamine is 100:1000.

[0016] As a further preferred technical solution of the present invention, in step S3, the calcination temperature is 900°C.

[0017] According to another aspect of the present invention, the present invention also provides a ceria in-situ linked Anderson type Mo-Fe anchored nitrogen-doped carbon nanotube, which is prepared by the above method.

[0018] According to another aspect of the present invention, the present invention also provides an application of ceria in-situ linked Anderson-type Mo-Fe anchored nitrogen-doped carbon nanotubes as an electrocatalyst in oxygen reduction reaction under alkaline or acidic conditions, or as an electrocatalyst in hydrogen evolution reaction under alkaline conditions.

[0019] As a further preferred technical solution of the present invention, cerium dioxide in-situ links Anderson-type Mo-Fe anchored nitrogen-doped carbon nanotubes as an electrocatalyst and is used in a metal-air battery. The preferred metal-air battery is a zinc-air battery, which uses CeO2 in-situ links Anderson-type Mo-Fe anchored nitrogen-doped carbon nanotubes as an air cathode, a zinc plate as an anode, and an alkaline solution or an acidic solution as an electrolyte.

[0020] Compared with the prior art, the present invention adopts the above technical solution to achieve the following beneficial effects:

[0021] (1) The present invention synthesizes CeO2-Anderson MoFe-N / C for the first time, using CeO2 as an in-situ connector to assemble the Anderson-type Mo-Fe precursor into a chain-like structure, thereby achieving efficient bonding with nitrogen-doped carbon nanotubes. First, the unique oxygen storage and release capacity of CeO2 is cleverly utilized to make CeO2-Anderson MoFe-N / C rich in a large number of oxygen vacancy defects, more carbon defects and graphitized carbon, which enhances the electron transfer ability and is conducive to the electrocatalytic process; secondly, CeO2 helps to stabilize more nitrogen sources during the synthesis of the catalyst, so that the N element can effectively establish a stable connection with the Mo and Fe elements, forming more nitrogen-containing active sites, promoting the breaking of the O-O bond of O2, and accelerating the O2 transmission during the oxygen reduction reaction and the adsorption in the hydrogen evolution reaction; finally, the addition of CeO2 can in situ generate a chain-like Anderson-type Mo-Fe topological structure, which is perfectly anchored on the nitrogen-doped carbon nanotubes through the Mo-C bond, and the enhanced electron transfer between metals effectively regulates the electronic structure of CeO2-Anderson MoFe-N / C and improves its conductivity.

[0022] (2) The CeO2-Anderson MoFe-N / C of the present invention has high catalytic activity. In 0.1 M KOH alkaline solution, the half-wave potential of the oxygen reduction reaction reaches 0.90 V, which is superior to the commercial Pt / C (20%). In 0.5 M H2SO4 acidic solution, the half-wave potential of the oxygen reduction reaction reaches 0.76 V. CeO2-Anderson MoFe-N / C effectively improves the catalyst stability and can still maintain high reduction activity after 1000 cycles. In the performance of zinc-air batteries, the maximum power density of CeO2-Anderson MoFe-N / C is much greater than the maximum power density of the commercial Pt / C+RuO2 catalyst, and the voltage gap of CeO2-Anderson MoFe-N / C is smaller than the voltage gap of Pt / C+RuO2, which has excellent oxygen reduction catalytic performance.

[0023] (3) In the hydrogen evolution reaction, CeO2-Anderson MoFe-N / C of the present invention has a current density of 10 mA·cm -2 The overpotential is only 81 mV, and the catalytic performance of hydrogen evolution reaction is better than most non-precious metal catalysts reported so far.

[0024] (4) The present invention has the characteristics of simple preparation process, no three wastes, environmental friendliness, novel structure, etc. It provides a practical strategy for the development of high-performance, low-cost zinc-air battery materials, oxygen reduction reaction and hydrogen evolution reaction, and provides ideas for the design of efficient green energy storage devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0026] Figure 1 (ab) scanning electron microscope images, (cd) transmission electron microscope images, and (e) contact angle test image of the CeO2-AndersonMoFe-N / C material with a strip-shaped Anderson-type topological structure linked by CeO2 synthesized in Example 1.

[0027] Figure 2 Ce(OH) synthesized in Example 1 δ+ -Infrared spectrum of Anderson MoFe.

[0028] Figure 3 LSV polarization curves of the oxygen reduction test of CeO2-Anderson MoFe-N / C and commercial Pt / C (20%) catalysts synthesized in Example 1 in 0.1 M KOH (a) and 0.5 M H2SO4 solutions (b); (c) is the cyclic stability test graph of CeO2-Anderson MoFe-N / C and commercial Pt / C (20%) catalysts in 0.1 M KOH alkaline solution after 1000 cycles.

[0029] Figure 4 Schematic diagram of the zinc-air battery prepared based on CeO2-Anderson MoFe-N / C synthesized in Example 1 (a); (bc) polarization (Vj) curves and power density (Pj) curves as well as charge and discharge polarization curves based on commercial Pt / C (20%) catalyst and CeO2-Anderson MoFe-N / C catalyst, respectively; (d) 100,000s test of battery open circuit voltage; (e) Photo of a zinc-air battery with an open circuit voltage of 1.48 V; (f) Photo of a light sign lit by the power supplied by the homemade zinc-air battery.

[0030] Figure 5 LSV curves of CeO2-Anderson MoFe-N / C synthesized in Example 1 and commercial Pt / C (20%) catalyst in HER reaction.

[0031] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION

[0032] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0033] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0034] The Nafion solution, commercial Pt / C (20%) and RuO2 catalyst used in the following experiments were purchased from McLean Company (CAS: 31175-20-9, 7440-06-4 and 12036-10-1, respectively); the mass ratio of commercial Pt / C+RuO2 catalyst was 1:1.

[0035] Embodiment 1:

[0036] The preparation method of the in-situ linked Anderson-type Mo-Fe anchored nitrogen-doped carbon nanotubes by ceria provided in this embodiment is as follows:

[0037] Step 1, Ce(OH) δ+ - Preparation of Anderson MoFe:

[0038] Accurately weigh 3.0 mmol of ferric nitrate nonahydrate, 0.34 mmol of cerium nitrate hexahydrate, and 18.0 mmol of ammonium molybdate tetrahydrate, dissolve them in 50 mL of boiling deionized water, keep the reaction at 80 °C for 2 hours, cool to room temperature after the reaction is completed, and centrifuge and dry to obtain Ce(OH) δ+ -Anderson MoFe material.

[0039] Depend on Figure 2 The infrared spectrum of the Mo-based polyoxometalate Ce(OH) was successfully synthesized. δ+ -Anderson MoFe material.

[0040] Step 2: Ce(OH) δ+ - Preparation of Anderson MoFe-N / C:

[0041] The Ce(OH) prepared in step 1 δ+ -Anderson MoFe material (0.1 g) was dispersed in 10 mL of deionized water, and then 20 mg of carbon nanotubes and 80 mg of glucose were added. The mixture was stirred with a magnetic stirrer for 20 minutes to make it uniformly mixed. The resulting suspension was transferred to a polytetrafluoroethylene reactor and placed in an electric heating blast drying oven at 180 °C for 15 hours. After the reaction was completed, it was cooled to room temperature, washed with deionized water, and dried to obtain Ce(OH) δ+ -Anderson MoFe-N / C material.

[0042] Step 3, Preparation of CeO2-Anderson MoFe-N / C:

[0043] 0.1 g CeO2-Anderson MoFe-N / C material and 1.0 g melamine were fully ground, mixed and evenly spread in a porcelain boat. After calcination at 900 °C for 1 hour under N2 atmosphere, they were naturally cooled to room temperature to obtain CeO2-Anderson MoFe-N / C material with a strip-shaped Anderson-type topological structure linked by CeO2.

[0044] See also Figure 1 As shown in the SEM image ( Figure 1 ab) CeO2-Anderson MoFe-N / C and carbon nanotubes have the same tendency, and both are evenly wrapped. Transmission electron microscopy images ( Figure 1 cd) shows the presence of the above-mentioned carbon defects and uniform nanoparticle loading on the carbon nanotubes. The contact angle test results show that CeO2-Anderson MoFe-N / C ( Figure 1 e) has a contact angle of 0.00°, indicating good hydrophilicity. Specifically, the introduction of CeO2 significantly improves the surface wettability of the catalyst and reduces the contact angle, indicating that the CeO2-Anderson MoFe-N / C surface has stronger hydration and higher hydrophilicity. This improved hydrophilicity helps to improve the contact efficiency of the catalyst in the electrochemical reaction, promotes the rapid adsorption and reaction of reactants (water or oxygen) with the catalyst surface, and further enhances its catalytic performance in oxygen reduction reaction and hydrogen evolution reaction.

[0045] Figure 2 Shows Ce(OH) δ+ -Infrared spectrum of Anderson MoFe. The results show that the -1 The broad peak is attributed to the stretching vibration of hydroxyl (-OH), which comes from the Ce(OH) part or adsorbed water molecules; ~1600 cm-1 The peak corresponds to the HOH bending vibration of water molecules; ~1400-1500 cm -1 The peak is related to the bending vibration of CH; ~1100-1000 cm -1 The absorption peak at 900 cm can be attributed to the stretching vibration of Mo-O, Fe-O or PO bonds, which is related to the polymetallic oxygen cluster characteristics in the Anderson structure; -1 The absorption peaks below and above are usually associated with the vibration of Mo-O-Mo or Fe-O-Mo bridge bonds. δ+ Modification, but the overall structure of the sample is not completely destroyed. The modification is the introduction of new functional groups (such as Ce-OH or metal-oxygen interactions) or the adjustment of certain local coordination environments, which provides a basic platform for the optimization of catalytic performance while retaining the characteristics of the original material.

[0046] The catalytic performance of the CeO2 in-situ linked Anderson type Mo-Fe anchored nitrogen-doped carbon nanotubes (CeO2-Anderson MoFe-N / C) prepared in this example as a catalyst is tested below:

[0047] 1) Oxygen reduction activity test:

[0048] All electrochemical tests were performed at room temperature using a CHI 760E electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd.) with a three-electrode setup. A rotating ring disk electrode (RRDE-3A) with an area of ​​0.0707 cm was used as the working electrode. 2 A saturated calomel electrode (SCE) with a diameter of 3.0 mm was used as the reference electrode and a carbon rod as the counter electrode. The surface of the glassy carbon electrode was polished before the electrochemical reaction test. 5 mg CeO2-Anderson MoFe-N / C was dispersed in a mixed solution of 250 μL ultrapure water and 250 μL ethanol, and 25 μL (0.05%) Nafion adhesive was added, and it was ultrasonically treated for 30 minutes to obtain solution 1; then 2 μL solution 1 was evenly drop-coated on the working electrode and dried at room temperature. Then, commercial Pt / C (20%) catalyst was used as the control group and the comparative test was carried out in the same way. Specifically, 5 mg Pt / C (20%) was dispersed in a mixed solution of 250 μL ultrapure water and 250 μL ethanol, and 25 μL (0.05%) Nafion adhesive was added, and it was ultrasonically treated for 30 minutes to obtain solution 1; then 2 μL solution 1 was evenly drop-coated on the working electrode and dried at room temperature.

[0049] Oxygen reduction tests were performed in O2-saturated 0.1 M KOH or 0.5 M H2SO4 over a potential range of -0.9 to 0.2 V (vs. Hg / Hg2Cl2). The rotation speed was 1600 rpm and the voltage was 10 mV·s -1 The linear sweep voltammetry (LSV) curve was measured at a scan rate of Figure 3 As shown in Figure 2, the CeO2-Anderson MoFe-N / C catalyst exhibits excellent catalytic performance and outstanding stability in the oxygen reduction reaction. Under alkaline conditions, its half-wave potential is close to 0.90 V, which is higher than that of the commercial Pt / C catalyst, showing stronger catalytic activity ( Figure 3 a); Under acidic conditions, its half-wave potential is about 0.76 V, which is comparable to that of Pt / C catalyst and shows excellent catalytic performance ( Figure 3 b). In addition, after 1000 cycles, the catalytic activity of CeO2-Anderson MoFe-N / C remained almost unchanged, showing extremely high stability, while the performance of the commercial Pt / C catalyst decreased significantly, showing its poor stability ( Figure 3 c). Overall, CeO2-Anderson MoFe-N / C outperforms the commercial Pt / C catalyst in terms of catalytic activity and stability in oxygen reduction reaction.

[0050] 2) Applied to performance testing of air batteries:

[0051] The relevant tests of the homemade zinc-air battery were carried out at room temperature using a CHI 760E electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd.). 5 mg CeO2-Anderson MoFe-N / C was dispersed in 250 μL ethanol, 250 μL deionized water and 25 μL (0.05%) Nafion solution to obtain solution 1. The above solution 1 was then coated on one side of a carbon paper (Sigracet GDL 29BC) as an air cathode, a Zn foil was used as a metal anode, and a 6.0 M KOH solution was used as an electrolyte to assemble a zinc-air battery ( Figure 4 a is a schematic diagram of the assembled zinc-air battery). The maximum power density of CeO2-Anderson MoFe-N / C is 147.6 mW·cm -2 ; much larger than the commercial Pt / C+RuO2 catalyst (103.5 mW·cm -2 ) maximum power density. The voltage gap of CeO2-Anderson MoFe-N / C is smaller than that of Pt / C+RuO2, indicating that it has excellent oxygen reduction catalytic performance ( Figure 4 bc). Figure 4de shows that the open circuit voltage of the zinc-air battery prepared by CeO2-Anderson MoFe-N / C is 1.48 V; Figure 4 f is a photo of a light sign being lit up by electricity powered by a homemade zinc-air battery.

[0052] 3) Hydrogen evolution reaction activity test:

[0053] All electrochemical tests were performed at room temperature using a three-electrode setup using a CHI 760E electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd.). A glassy carbon electrode with an area of ​​0.0707 cm was used as the working electrode. 2 A saturated calomel electrode (SCE) (3.0 mm in diameter) was used as the reference electrode and a carbon rod as the counter electrode. The surface of the glassy carbon electrode was polished before the electrochemical reaction test. 5 mg CeO2-Anderson MoFe-N / C was dispersed in a mixed solution of 250 μL ultrapure water and 250 μL ethanol and 25 μL (0.05%) Nafion adhesive was added and ultrasonicated for 30 min to obtain solution 1. 2 μL of solution 1 was evenly drop-coated on the working electrode and dried at room temperature. A commercial Pt / C (20%) catalyst was prepared in the same manner. The hydrogen evolution reaction test was carried out in 1.0 M KOH saturated with N2 at a potential range of -1.0 to 1.0 V (relative to Hg / Hg2Cl2). The reaction was carried out at 10 mV·s -1 The linear sweep voltammetry (LSV) curve was measured at a scan rate of Figure 5 As shown, CeO2-Anderson MoFe-N / C was heated to 10 mA cm-1 in 1.0 M KOH. -2 The overpotential is only 81 mV, and the catalytic performance of hydrogen evolution reaction is better than most non-precious metal catalysts reported so far.

[0054] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.

Claims

1. A method for preparing in-situ linked Anderson-type Mo-Fe anchored nitrogen-doped carbon nanotubes by ceria, characterized in that: The following steps are involved: S1. Dissolve ferric nitrate nine hydrate, cerium nitrate six hydrate and ammonium molybdate four hydrate in boiling deionized water, then react at 80 ℃-90 ℃, centrifuge and dry to obtain Mo-based polyoxometalate Ce(OH) δ+ -AndersonMoFe material; S2, adding glucose and carbon nanotubes into deionized water, and adding Ce(OH) δ+ -Anderson MoFe materials were mixed and reacted by hydrothermal synthesis. The reactants were washed and dried to obtain Ce(OH) δ+ -Anderson MoFe-N / C material; S3, Ce(OH) δ+ -Anderson MoFe-N / C material and melamine are fully ground and mixed evenly, and calcined under N2 or inert atmosphere to obtain CeO2-Anderson MoFe-N / C material with a strip-shaped Anderson-type topological structure linked by CeO2, that is, Anderson-type Mo-Fe anchored nitrogen-doped carbon nanotubes in situ linked by ceria.

2. The method for preparing the in-situ linked Anderson-type Mo-Fe anchored nitrogen-doped carbon nanotubes by ceria according to claim 1, characterized in that: In step S1, the usage ratio of ferric nitrate nonahydrate, cerium nitrate hexahydrate, and ammonium molybdate tetrahydrate is 0.95-0.5 mol: 0.05-0.5 mol: 5.7-3 mol.

3. The method for preparing the in-situ linked Anderson type Mo-Fe anchored nitrogen-doped carbon nanotubes by ceria according to claim 1, characterized in that: In step S2, the reaction temperature of the hydrothermal synthesis method is 180°C.

4. The method for preparing the in-situ linked Anderson type Mo-Fe anchored nitrogen-doped carbon nanotubes by ceria according to claim 1, characterized in that: In step S2, the dosage ratio of carbon nanotubes, glucose and deionized water is 10-32 mg: 60-86 mg: 5-17 mL.

5. The method for preparing the in-situ linked Anderson type Mo-Fe anchored nitrogen-doped carbon nanotubes by ceria according to claim 1, characterized in that: In step S3, Ce(OH) δ+ -The molar ratio of Anderson MoFe-N / C material to melamine is 100:1000.

6. The method for preparing the in-situ linked Anderson-type Mo-Fe anchored nitrogen-doped carbon nanotubes by ceria according to claim 1, characterized in that: In step S3, the calcination temperature is 900°C.

7. A ceria in-situ linked Anderson type Mo-Fe anchored nitrogen-doped carbon nanotubes, characterized in that: The method is prepared by any one of claims 1 to 6.

8. Use of the ceria in-situ linked Anderson type Mo-Fe anchored nitrogen-doped carbon nanotubes as claimed in claim 7 as an electrocatalyst.

9. The use according to claim 8, characterized in that: The cerium dioxide in-situ linked Anderson-type Mo-Fe anchored nitrogen-doped carbon nanotubes are used as electrocatalysts in metal-air batteries.